2021
DOI: 10.1016/j.ijhm.2020.102701
|View full text |Cite
|
Sign up to set email alerts
|

CEO letters: Hospitality corporate narratives during the COVID-19 pandemic

Abstract: Highlights This study content-analyzed 57 CEO letters published by hospitality companies during the COVID-19 pandemic. The findings indicated that rational and credible appeals were prevalent in COVID-19 hospitality corporate narratives. Hospitality organizations largely relied on defensive tactics to plausibly claim their response strategies to COVID-19. Assertive tactics were employed to convey the character of businesses as credible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 46 publications
4
58
0
3
Order By: Relevance
“…Between our two studies and in line with recent literature focused on understanding the new communicational paradigm for hospitality firms ( Hu et al, 2021 ; Im et al, 2021 ; Shin and Kang, 2020 ), we have confirmed that during the COVID-19 pandemic era, hotels’ communications about how they ensure clean and safe spaces are available for guests are an essential part of the tourist–hotel relationship.…”
Section: Discussionsupporting
confidence: 87%
“…Between our two studies and in line with recent literature focused on understanding the new communicational paradigm for hospitality firms ( Hu et al, 2021 ; Im et al, 2021 ; Shin and Kang, 2020 ), we have confirmed that during the COVID-19 pandemic era, hotels’ communications about how they ensure clean and safe spaces are available for guests are an essential part of the tourist–hotel relationship.…”
Section: Discussionsupporting
confidence: 87%
“…A few studies have investigated CEOs' letters by applying the Aristotelian concept of persuasive rhetoric [8,38,41,42]. In these letters, the element logos refers to how writers logically present problems, support arguments and suggest conclusions.…”
Section: Social Accounting Communication and The Use Of Rhetoric Durimentioning
confidence: 99%
“…The element pathos concerns how writers focus on the readers' values and directly involve the readers in providing an answer, while the element ethos regards the writers' authority and integrity [41]. For instance, [8] conducted a study to identify corporate narrative strategies during the spread of COVID-19 in the hospitality sector. They performed a content analysis of CEO letters published by hospitality companies during the COVID-19 outbreak because of the crucial role played by the CEO in promoting corporate image and reputation [43,44].…”
Section: Social Accounting Communication and The Use Of Rhetoric Durimentioning
confidence: 99%
See 1 more Smart Citation
“…Only this field of activity is marked by a large number of dangerous situations. World experience in hotel industry creation indicates that neglecting or downplaying the size of entrepreneurial risk while designing a tactical and strategic strategy for the growth of a hotel business or the entire industry as a whole prevents social development, triggering deflation or even recession in the country's entire economic system (Im et al, 2020).…”
Section: Institutional Aspects Of Risk Strategic Managementmentioning
confidence: 99%